Analysis of Engineering Design Process (EDP) Skills Through the Application of STEM-PJBL Based LKPD for High School Students on Archimedes Law Material - Afkarina, Naili; Djoko Lesmono, Albertus; Nuraini, Lailatul (Proceeding of International Joint Conference on UNESA, 2025)
Engineering Design Process (EDP) skills are one of the skills that students must have in the 21st century. Engineering is one of the components that has an important role in training students related to the skill of designing solutions to life's problems. However, the facts show that there is still a lack of learning in schools that train and teach Engineering Design Process (EDP) skills that should be part of the physics learning process. The purpose of this study is to analyze Engineering Design Process (EDP) skills through the application of STEM-PjBL-based LKPD to Archimedes Law material. The research design used is a case study research design with research stages consisting of problem identification, literature search, determination of research objectives, data collection, data analysis and interpretation, and finally reporting. The results of the study show that EDP skills in the indicator of gathering pertinent information are categorized as good, while defining the problem, generating multiple solutions, analyzing and selecting a solution, and test and implement the solution are in the very good category. Based on the results of the research, it can be concluded that most of the Engineering Design Process (EDP) skills possessed by students are good.